Thermal Disparity among Fingers and Its Amelioration by CO2-Water Bathing in Connective Tissue Disease Patients - Shigeko Inokuma; Yasuo Kijima (International Journal of Vascular Medicine)
Objective. Correlation between a low finger temperature and thermal disparity among fingers was studied in connective tissue disease (CTD) patients. Whether the thermal disparity may be ameliorated by hand immersion in a warm carbon dioxide- (CO2-) water bath was analyzed. Methods. CTD patients with suspected peripheral circulation disorder underwent a thermography test. From before to 30 min after hand immersion in CO2-water (CO2 bathing; 1000 ppm CO2, 42°C, 10 min), the nailfold temperatures were measured. The mean temperature (m-Temp) and the coefficient of variation of the temperature (CV=SD/m‐Temp of one hand; the mean of CVs of both hands was adopted as the indicator of thermal disparity) were monitored. The correlation between m-Temp and CV was also analyzed. Results. Forty-seven (45 females and 2 males) patients were included, 32 of whom had Raynaud’s phenomenon. The m-Temp was 30.8±3.0°C at the baseline, increased to 35.3±1.0°C immediately after CO2 bathing, and remained significantly higher than that at the baseline until 30 min after (32.1±1.9°C). The CV was 0.0291±0.0247 at the baseline, decreased to 0.0135±0.0039 immediately after CO2 bathing, and remained significantly lower than the baseline until 30 min after (0.0163±0.0143). Between m-Temp and CV, a negative correlation was observed throughout the measurements. Conclusion. Thermal disparity was observed at baseline measurement in CTD patients. Warm CO2 bathing markedly ameliorated the disparity, and this amelioration remained until after 30 min. Throughout the observation, the lower the m-Temp, the more severe the thermal disparity among fingers.